Popperian Hayek or Hayekian Popper? - Jo\~ao Pinheiro da Silva (Economic Thought, 2021)
Friedrich Hayek was a fervent advocate of the methodological specificity of the social sciences. However, given his contact with Karl Popper, several historians and philosophers have characterised his final position as Popperian, that is, a position that would have accepted the unity of the scientific method. A closer look at Hayek's philosophy and Popper's own intellectual course shows that such a thesis is based on some misconceptions that can be overcome by taking the Hayekian concept of 'spontaneous order' as the foundation of a methodology immune to any kind of methodological monism, and focusing on Popper's late works that reveal a loosening of his defense of methodological unity.
Keywords: B2; B3; B4; 330; Hayek; Popper; spontaneous order; methodological monism; social sciences